Application of a Numerical Moving Boundary Model for Prediction of Bubble Growth Rate in Boiling of PureLiquids and Miscible Binary Mixture - Hussain Tarrad, Ali (Journal of Engineering and Sustainable Development, 2005)
This investigation deals with the estimation of bubble growth rate during nucleate pool boiling of pure liquids and miscible wide boiling range binary mixture such as n-Pentane/Tetradecene mixture. Understanding the process of heat exchange between the heating surface and the adjacent liquid during boiling should start from the ability to understand the mechanism of bubble growth rate and departure parameters (diameter and frequency). For binary mixtures, the mass balance of the more volatile component (n-Pentane) and energy balance at the vapor/liquid interface were used to predict the bubble radius, R(t), as a function of time. Whereas, for pure liquids the energy balance at the bubble boundary was used to estimate the bubble radius together with the temperature distribution in the liquid domain. The bubble growth rate of binary mixtures predicted by this model was compared with existingtheories. The discrepancy in the bubble growth constant between this analysis and those of other investigators was explained and verified by the present model. The model of pure liquids showed well agreement with available experimental data.